EXPANSION OF INTERPOLATION IN THE OCTONIONS CONTEXT - Norouzi, Samaneh; Akar, Mutlu (EDITURA BIBLIOTHECA-BIBLIOTHECA PUBL HOUSE, 2026)
This paper extends the notion of interpolation from the quaternionic framework to the octonionic setting. By establishing a well-adapted algebraic basis, we examine how replacing the quaternion space with octonions influences the generated curves. The obtained curves in the octonionic space are not only differentiable but also display smoother behavior compared to those generated by corresponding methods in the quaternionic case. Moreover, the convergence is achieved with less iteration.
Keywords: Octonion curve; rotation; Clifford algebras; curve blending; Science & Technology - Other Topics